2013
DOI: 10.1097/nur.0b013e3182a0baec
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices of Turkish Intern Nurses Regarding Physical Restraints

Abstract: Although there are studies on the knowledge, attitudes, and practices of nurses working in the fields of elderly care, rehabilitation, and psychiatry in acute care units, there are no studies investigating intern nurses and other nursing students. However, intern nurses about to begin their careers should make accurate decisions regarding the use of physical restrains if they are to ensure patient safety and to fulfill this application effectively in their professional lives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
21
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 33 publications
16
21
1
3
Order By: Relevance
“…It made me feel so guilty. Our findings were also consistent with those in the studies of Karagozoglu et al (2013) and Suen (1999). In fact, this question assesses their awareness of the psychological impact of physical restraint use on residents and their relatives.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It made me feel so guilty. Our findings were also consistent with those in the studies of Karagozoglu et al (2013) and Suen (1999). In fact, this question assesses their awareness of the psychological impact of physical restraint use on residents and their relatives.…”
Section: Discussionsupporting
confidence: 93%
“…2.76 (0.56) 13. Regrettably, the findings from our survey show that nursing staff's awareness of residents' rights remains low, which is similar to the previous findings (Eskandari et al, 2017;Karagozoglu et al, 2013;Suen, 1999). replied that "a physical restraint tool is a type of security vest or clothing which can prevent residents from getting hurt," and also "residents are not allowed to refuse to be placed in a restraint."…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, most of the nurses had negative attitudes regarding important areas of physical restraint use. These findings are consistent with some other studies (Azab & Abu Negm, ; Karagozoglu et al., ; McCabe, Alvarez, McNulty, & Fitzpatrick, ). For example, more than half of nurses disagreed with the statement ‘I feel that family members have the right to refuse the use of physical restraint’.…”
Section: Discussionsupporting
confidence: 93%
“…However, nurses showed certain important misunderstandings regarding physical restraint use. These findings are consistent with other studies that revealed almost moderate level of knowledge of nurses regarding physical restraint use (Azab & Abu Negm, ; Karagozoglu, Ozden, & Yildiz, ; Suen et al., ). We found in agreement with other studies (De Jonghe et al., ; Janelli et al., ) that many nurses stated that physical restraints does not require a physician's order.…”
Section: Discussionsupporting
confidence: 92%